Perceptions of Household Income and Subjective Well-Being of Children in China - Xie, Shenghua; Hakovirta, Mia; Gao, Yunjiao (Child indicators research, 2020)
The effects of income poverty and material deprivation on the subjective well-being of children have been widely explored. However, little is known about how children’s perceptions of household income may influence their subjective well-being. Using questionnaire survey data on children from 10 schools in Wuhan, China, this study aims to explore this issue. The results indicate that while perceptions of objective household income show no significant association with the subjective well-being of children, perceptions of subjective household income exhibit a significant positive relationship with it. In addition, there is an interaction effect of perceptions of subjective household income and bullying victimization on the subjective well-being of children. That is, for children who have better perceptions of subjective household income, the more bullying victimization they suffer, the worse their subjective well-being. The results of this study suggest that how perceptions of household income influence the subjective well-being of children is in line with some of the studies on the relationship between income and the subjective well-being of adults. However, some traits such as the moderating effect of bullying victimization on the association between perceptions of subjective household income and subjective well-being are worthy of special attention. Moreover, the findings of this study indicate that the relationship between income and subjective well-being may be shaped in childhood, suggesting that future research devoted to revealing this mechanism should pay more attention to the influence of early life experiences.